2019
DOI: 10.1049/mnl.2018.5035
|View full text |Cite
|
Sign up to set email alerts
|

Highly photoactive Ag‐based urchin‐like E‐g‐C 3 N 4 /TiO 2 ternary composite photocatalyst

Abstract: Herein, silver (Ag)-based urchin-like E-graphite carbon nitride/titanium dioxide (E-g-C 3 N 4/ TiO 2) ternary composite was successfully synthesised via hydrothermal process and it showed excellent photocatalytic activity. The large interfacial contact between threedimensional (3D) urchin-like TiO 2 (UT) and g-C 3 N 4 leads to high photocatalytic activity, compared with pure 3D UT. To enlarge the response of light and enhance the charge carriers' transfer, the Ag nanoparticles with average sizes of 13 nm were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The construction of ternary Ag/TiO 2 /g-C 3 N 4 heterostructures represents a very promising strategy for achieving the enhanced photocatalytic performance of semiconductor nanocomposites under visible light irradiation [ 43 , 45 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. Various approaches for the synthesis of Ag/TiO 2 /g-C 3 N 4 nanocomposites have been reported in the literature.…”
Section: Ag/tio 2 /G-c 3 N ...mentioning
confidence: 99%
See 3 more Smart Citations
“…The construction of ternary Ag/TiO 2 /g-C 3 N 4 heterostructures represents a very promising strategy for achieving the enhanced photocatalytic performance of semiconductor nanocomposites under visible light irradiation [ 43 , 45 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. Various approaches for the synthesis of Ag/TiO 2 /g-C 3 N 4 nanocomposites have been reported in the literature.…”
Section: Ag/tio 2 /G-c 3 N ...mentioning
confidence: 99%
“…One of these proposes the preparation of a mixture of Ag, TiO 2 and g-C 3 N 4 precursors and the synthesis of an Ag/TiO 2 /melamine nanocomposite at 70 °C, followed by calcination of the nanocomposite at 550 °C, to produce g-C 3 N 4 from melamine ( Figure 11 a) [ 126 ]. Another strategy is to mix previously synthesized TiO 2 and g-C 3 N 4 , followed by the addition of an AgNO 3 precursor and synthesis of Ag NPs in the presence of a g-C 3 N 4 and TiO 2 mixture or previously prepared TiO 2 /g-C 3 N 4 nanocomposite ( Figure 11 b1,b2) [ 45 , 115 , 123 , 124 ]. A TiO 2 /g-C 3 N 4 composite was also prepared by the synthesis of g-C 3 N 4 from a suitable precursor in the presence of TiO 2 or through the synthesis of TiO 2 from a suitable precursor in the presence of g-C 3 N 4 , followed by the synthesis of Ag NPs from an AgNO 3 precursor in a reduction reaction in the presence of TiO 2 /g-C 3 N 4 nanocomposite ( Figure 11 c1,c2) [ 108 , 116 , 117 ].…”
Section: Ag/tio 2 /G-c 3 N ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao et al developed a heat transfer model to efficiently and reliably predict the temperature evolution of the printed materials and the waiting time between the layers for any input geometry. [ 29 ] Furthermore, they proposed a heuristic tool path planning method. [ 30 ] It was found that the tool path planning highly affects the spatial and temporal temperature distribution of the being printed part, and the optimized tool path planning can effectively improve the uniformity of the temperature distribution.…”
Section: Ice 3d Printingmentioning
confidence: 99%